2013
DOI: 10.1155/2013/261593
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Reduces Tau Phosphorylation in Rat Hippocampal Slices by Targeting NR2A Receptors, GSK3β, and PKC Activities

Abstract: The molecular mechanisms that regulate Tau phosphorylation are complex and currently incompletely understood. In the present study, pharmacological inhibitors were deployed to investigate potential processes by which the N-methyl-D-aspartate (NMDA) subtype of glutamate receptors modulates Tau phosphorylation in rat hippocampal slices. Our results demonstrated that Tau phosphorylation at Ser199-202 residues was decreased in NMDA-treated hippocampal slices, an effect that was not reproduced at Ser262 and Ser404 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…Second, PKC has been implicated in tau phosphorylation indirectly through its ability to phosphorylate and inactivate glycogen synthase kinase-3β (GSK-3β), thereby reducing tau phosphorylation catalyzed by this kinase [68]. PKC has also been linked to N-methyl-d-aspartate receptor (NMDAR)-mediated reduction in tau phosphorylation [69]. Overall, PKC's regulation of cytoskeleton dynamics in the brain plays a critical role not only in synapse formation and maintenance, but also in the functions of non-neuronal cells such as endothelial and glial cells [49].…”
Section: Regulation Of the Cytoskeleton: Marcks Gap43 And Taumentioning
confidence: 99%
“…Second, PKC has been implicated in tau phosphorylation indirectly through its ability to phosphorylate and inactivate glycogen synthase kinase-3β (GSK-3β), thereby reducing tau phosphorylation catalyzed by this kinase [68]. PKC has also been linked to N-methyl-d-aspartate receptor (NMDAR)-mediated reduction in tau phosphorylation [69]. Overall, PKC's regulation of cytoskeleton dynamics in the brain plays a critical role not only in synapse formation and maintenance, but also in the functions of non-neuronal cells such as endothelial and glial cells [49].…”
Section: Regulation Of the Cytoskeleton: Marcks Gap43 And Taumentioning
confidence: 99%
“…Although the toxic effects of Aβ are widely known, the study into the evolutionary benefit of Aβ as an antioxidant is in its infancy [127]. PKC isoforms also serve as potent regulators of tau phosphorylation at serine 199–202 [9]. Importantly, PKCα regulates tau binding to tubulin within axons.…”
Section: Pkc and Admentioning
confidence: 99%
“…PKCγ also contributes to the preservation of synaptic plasticity [8]. Besides the role that PKC isoforms play in memory formation, they also have important functions as tau kinases [9]. In particular, age-related changes in PKC translocation have been linked to tau hyperphosphorylation and the phosphorylation of glycogen synthase kinase 3β (p-GSK3β) [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GSK-3β activity is increased in response to phencyclidine, a NMDA receptor antagonist, in rat hippocampus, striatum and frontal cortex 97 . It was also shown that administration of NMDA resulted in increased serine phosphorylation of GSK-3β in rats 98 . A limited number of studies have indicated that NMDA receptor stimulation enhanced GSK-3β phosphorylation whereas its blockade increased GSK-3β activity.…”
mentioning
confidence: 94%